Using E-Learning Platforms in Teaching Islamic Education - Alhammad, Noorjihan; Awae, Fareed; Yussuf, Ahmad; Al-Awami, Ahmed Yahya Mohsen; Hayiwaesorhoh, Makueta; Chehama, Aman (Journal of Islamic Educational Research, 2025)
This article aims to highlight the importance of utilizing electronic learning platforms in teaching Islamic education. It begins by reviewing the concept and objectives of Islamic education, and then discusses the characteristics, components, and advantages of e-learning platforms. The paper emphasizes their role in facilitating learning and enhancing interaction between teachers and students. It further explores the key benefits of using these platforms such as improving learning efficiency and overcoming time and place constraints while also presenting the justifications for their use, like flexibility of access and ease of use. The article does not overlook the challenges associated with these platforms, including limited infrastructure, lack of technical training, and the reluctance of some educators. The study concludes that e-learning platforms are a promising and effective tool for improving Islamic education, provided a supportive environment is created and both teachers and learners are trained to use them effectively.